Modern perspectives on psychoses: dissociation, automatism, and temporality across exogenous and endogenous dimensions - Ricci, Valerio; Ciavarella, Maria Celeste; Marrangone, Carlotta; Messas, Guilherme; Maina, Giuseppe; Martinotti, Giovanni (Frontiers in Psychiatry, 2025)
Substance use and the emergence of Novel Psychoactive Substances (NPS) present a significant public health challenge and diagnostic dilemma, particularly in the context of psychosis. The increasing availability of psychoactive substances among youth has led to a rise in Substance Use Disorders (SUDs), with profound implications for mental health. This paper explores the psychopathological distinctions between substance-induced psychoses (SIPs) and endogenous psychoses, such as schizophrenia, from a phenomenological perspective. We emphasize three key aspects: dissociation, mental automatism, and temporality, to elucidate the underlying mechanisms of these conditions. Dissociation, as a psychopathological organizer, is central to exogenous psychoses, particularly those triggered by NPS. This phenomenon leads to a fragmentation of consciousness, detachment from reality, and disintegration of identity, distinct from the spaltung observed in endogenous psychoses. The concept of mental automatism, as theorized by De Clerambault, is also explored, highlighting its role in the early stages of exogenous psychoses, where cognitive disruptions precede delusions and hallucinations. Furthermore, the temporal experience in SIPs is characterized by a disconnection from past and future, trapping individuals in an “eternal present.” This contrasts with the fragmented temporality observed in schizophrenia, where patients struggle to maintain a coherent narrative of their lives. The phenomenological approach provides critical insights into the clinical differentiation between SIPs and Primary Psychotic Disorders (PPDs), emphasizing the need for targeted interventions that address the specific temporal and cognitive disruptions in substance-induced conditions. In conclusion, this paper underscores the importance of integrating phenomenological psychopathology into clinical practice, particularly in the face of the evolving landscape of substance use and psychosis. Understanding the distinct psychopathological mechanisms underlying SIPs can inform more accurate diagnoses and effective treatments, ultimately improving patient outcomes in the context of this growing public health issue.